TO THE QUESTION OF MAXIMIZING THE ENTERPRISES EFFICIENCY - V. Vasyaycheva (Вестник университета)
Many domestic enterprises are in crisis today. Modern managers are faced with reorganization problems of productive activities in order to increase the economic efficiency of the company functioning and growth of competitiveness. The article analyzes the economic activity of one of the enterprises of the Samara region, revealed deficiencies in its functioning and recommendations for their elimination.